Increasing Dividend Payout Ratio with Financial Performance Strategy and the Role of CEO in Indonesian Consumer Goods Company - Herlin Munthe; Cyntia Lee; Silkhe Hong; Flourencia Anggelinata (Enrichment : Journal of Management, 2022)
The objective of this study was to analyze the dividend decisions of consumer goods companies in Indonesia with the established financial performance strategy and involve the role of the Chief Executive Officer (CEO) in its implementation. The data for this study were derived from the financial statements of companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The population in this study is 209 companies in the Consumer Goods sector, of which 128 companies come from the Consumer Cyclicals sector and 92 companies in the Non-Cyclicals sector. The sampling technique used was purposive sampling. The research method is a quantitative approach with path analysis data method using Smart PLS. The findings revealed: 1) The number of CEOs has a positive and significant effect on profitability. 2) Leverage has a negative and significant effect on dividend distribution decisions. 3) Leverage has a negative and significant effect on profitability. 4) The number of CEOs moderated by profitability has a positive and significant effect on dividend distribution decisions. 5) Leverage and company size moderated by profitability have no effect on dividend distribution decisions.